Expanded Prospective Payment System and Use of and Outcomes with Home Dialysis by Race and Ethnicity in the United States - Shen, Jenny I; Erickson, Kevin F; Chen, Lucia; Vangala, Sitaram; Leng, Lynn; Shah, Anuja; Saxena, Anjali B; Perl, Jeffrey; Norris, Keith C (Clinical journal of the American Society of Nephrology, 2019)
We investigated whether the recent growth in home dialysis use was proportional among all racial/ethnic groups and also whether there were changes in racial/ethnic differences in home dialysis outcomes. This observational cohort study of US Renal Data System patients initiating dialysis from 2005 to 2013 used logistic regression to estimate racial/ethnic differences in home dialysis initiation over time, and used competing risk models to assess temporal changes in racial/ethnic differences in home dialysis outcomes, specifically: ( ) transfer to in-center hemodialysis (HD), ( ) mortality, and ( ) transplantation. Of the 523,526 patients initiating dialysis from 2005 to 2013, 55% were white, 28% black, 13% Hispanic, and 4% Asian. In the earliest era (2005-2007), 8.0% of white patients initiated dialysis with home modalities, as did a similar proportion of Asians (9.2%; adjusted odds ratio [aOR], 0.95; 95% confidence interval [95% CI], 0.86 to 1.05), whereas lower proportions of black [5.2%; aOR, 0.71; 95% CI, 0.66 to 0.76] and Hispanic (5.7%; aOR, 0.83; 95% CI, 0.86 to 0.93) patients did so. Over time, home dialysis use increased in all groups and racial/ethnic differences decreased (2011-2013: 10.6% of whites, 8.3% of blacks [aOR, 0.81; 95% CI, 0.77 to 0.85], 9.6% of Hispanics [aOR, 0.94; 95% CI, 0.86 to 1.00], 14.2% of Asians [aOR, 1.04; 95% CI, 0.86 to 1.12]). Compared with white patients, the risk of transferring to in-center HD was higher in blacks, similar in Hispanics, and lower in Asians; these differences remained stable over time. The mortality rate was lower for minority patients than for white patients; this difference increased over time. Transplantation rates were lower for blacks and similar for Hispanics and Asians; over time, the difference in transplantation rates between blacks and Hispanics versus whites increased. From 2005 to 2013, as home dialysis use increased, racial/ethnic differences in initiating home dialysis narrowed, without worsening rates of death or transfer to in-center HD in minority patients, as compared with white patients.